Giant Raman gain in silicon nanocrystals - Sirleto, Luigi (Nature Pub. Group, 2012)
Nanostructured silicon has generated a lot of interest in the past decades as a key material for silicon-based photonics. The low absorption coefficient makes silicon nanocrystals attractive as an active medium in waveguide structures, and their third-order nonlinear optical properties are crucial for the development of next generation nonlinear photonic devices. Here we report the first observation of stimulated Raman scattering in silicon nanocrystals embedded in a silica matrix under non-resonant excitation at infrared wavelengths (~1.5 μm). Raman gain is directly measured as a function of the silicon content. A giant Raman gain from the silicon nanocrystals is obtained that is up to four orders of magnitude greater than in crystalline silicon. These results demonstrate the first Raman amplifier based on silicon nanocrystals in a silica matrix, thus opening new perspectives for the realization of more efficient Raman lasers with ultra-small sizes, which would increase the synergy between electronic and photonic devices.